Pedals possible: a pilot study of adaptive cycling as a school-based rehabilitation intervention for students with disabilities - Brennan, Julia S.; Keller, Everette; Humanitzki, Elizabeth; Wade, Jessica Nichole; Catledge, Chad; Houston, Stephen; Beall, Jonathan; Dodds, Cynthia B. (Frontiers in Pediatrics, 2025)
IntroductionPediatric therapists in school-based practice can incorporate exercise promotion through adaptive cycling for children with disabilities who experience high levels of sedentary behavior and low levels of moderate to vigorous activity.MethodsThe impacts of an adaptive cycling pilot program for children with disabilities were investigated through a community-based participatory study. During an eight-week intervention, students had a goal of riding adaptive cycles three times a week for twenty minutes. Using a pre-and post-test design, primary outcomes included individualized goal attainment scaling (GAS) linked to students' individualized education plans (IEP) and the 6-minute cycling test (6MCT) measuring cycling distance. Secondary outcomes included cycling duration over time, assistance levels for pedaling and steering, a “happiness scale”, and overall program satisfaction of parents and teachers. To prevent harm, pain behavior was examined using the Faces, Legs, Activity, Cry, Consolability (FLACC).ResultsCycling had a positive impact on students with disabilities. No increased levels of pain behavior or adverse events were reported. Individual GAS T-score means significantly improved to 0.24 and program effectiveness achieved a T-score value of 50.53. The mean distance of 6MCT increased from 728.95 feet to 880.5 feet. Secondary measures also documented significant improvement. Parents and teachers reported high overall satisfaction.DiscussionAdaptive cycling can incorporate needed physical activity into the school day and also support the achievement of IEP goals, physical activity capacity, and emotional happiness. Scaling adaptive cycling programs for children with disabilities should be considered an excellent opportunity for educational growth, health, and well-being.